Workshop on lslamization of Knowledge - Tayyib Zain al-Abedin (International Institute of Islamic Thought, 1989)
The Workshop on Islarnization of Knowledge was held Shaban 20-22, 1409/March 27-29, 1989 at Usmanu Danfodiyo University in Sokoto, Nigeria. It was jointly sponsored by the University's Center for Islamic Studies, the Islamic Education Trust of Nigeria, the Muslim World League, and the International Institute of Islamic Thought (IIIT). The Center for Islamic Studies is headed by Dr. Omar Bellu, a specialist in Arab Islamic Studies who serves as the University's Vice-President, and as Secretary of the Nigerian Council of Scholars. The Islamic Education Trust is headed by Al-Hajj Ahmad Lemu, the Supreme Judge in Niger State and a prorrtlnent leader of the Islamic Movement in Nigeria who has established a number of Arabic Islamic Schools considered among the best for teaching Islamic and secular sciences. Objectives: The objective of the Workshop was to determine the means through which Usmanu Danfodiyo University, in cooperation with the Islamic Education Trust and other Islamic organizations could devise a program of action for the Islamization of general and higher education in Nigeria. It also aimed at revising curricula for various academic disciplines to accommodate Islamic perspectives and to meet Islamic norms; developing and producing teaching and reading materials for various disciplines; and developing staff to service the revised curricula along Islamic lines. The Workshop's attendance was restricted to the professors and teaching staff at Othman Dan Fodio University, and a number of youths from outside the university. On average, about eighty persons, including three or four women, attended each session. The participants paid special tribute to the martyr Isma'il al-Faruqi for his pioneering role in the Islarnization of Knowledge. The Seminar's Discussions: The first working session, chaired by Professor 'Abdul-Karirm Hussain, ...